Resistance to immunotherapeutic antibodies in cancer : strategies to overcome resistance - Bonavida, Benjamin (Resistance to Targeted Anti-Cancer Therapeutics, 2013)
The current application of antibody-meditated targeted therapy against cancer has resulted in significant objective clinical responses, prolongation of survival and even cures. More than 20 mAbs have been approved for human use targeting a range of different cancers. However, a major drawback of mAb therapeutics is that a subset of patients does not initially respond and another initially responding subset develops resistance to further treatments. At the present time, there are no effective therapies for these subsets of cancer patients. The analyses of underlying mechanisms responsible for resistance are necessary to develop and generate new targeted therapies that overcome the resistance. Resistance to Immunotherapeutic Antibodies in Cancer: Strategies to Overcome Resistance is a timely volume that deals with various mechanisms of resistance to anti-cancer mAbs therapeutics as well as it deals with novel approaches to overcome resistance. The reviews in this volume are written by highly qualified, established and experienced leaders in the field of resistance to anti-cancer mAbs.